2016
DOI: 10.1371/journal.pone.0146317
|View full text |Cite
|
Sign up to set email alerts
|

Can Continuous Positive Airway Pressure Reduce the Risk of Stroke in Obstructive Sleep Apnea Patients? A Systematic Review and Meta-Analysis

Abstract: Background and PurposeObstructive sleep apnea (OSA) has been shown to increase the risk of stroke. Although continuous positive airway pressure (CPAP) is considered the treatment of choice for OSA, whether treating OSA with CPAP reduces the risk of stroke remains unclear. We aimed to evaluate the effects of CPAP on incidence of stroke in patients with OSA.Materials and MethodsWe conducted a systematic review and meta-analysis of all published studies that provided the number of incident strokes in OSA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 36 publications
1
35
0
3
Order By: Relevance
“…7 However, CPAP is underused as a therapy for OSA even though investigators have demonstrated that CPAP may reduce the risk of atrial fibrillation or stroke. 46 Results of the current study also revealed that CPAP may reduce the risk of RA in patients with OSA depending on the extent of decrease of inflammatory mediators and oxidative stress.…”
Section: -11supporting
confidence: 64%
“…7 However, CPAP is underused as a therapy for OSA even though investigators have demonstrated that CPAP may reduce the risk of atrial fibrillation or stroke. 46 Results of the current study also revealed that CPAP may reduce the risk of RA in patients with OSA depending on the extent of decrease of inflammatory mediators and oxidative stress.…”
Section: -11supporting
confidence: 64%
“…Systematic reviews: Four studies were included [69][70][71][72]. The original studies included in the systematic reviews were of class I or II quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Sleep apnea is highly prevalent in patients with stroke or TIA, and OSA also is associated with increased risk for incident stroke (4648). There is some evidence that early CPAP therapy has positive effects on long-term survival in ischemic stroke patients with moderate-to-severe OSA (4648).…”
Section: Osa and Related Cvd: Effect Of Cpap Therapymentioning
confidence: 99%
“…There is some evidence that early CPAP therapy has positive effects on long-term survival in ischemic stroke patients with moderate-to-severe OSA (4648). Additionally, consistent with observational studies (4648), in a recent large RCT (49), those OSA patients who were adherent to CPAP therapy exhibited reduced risk of incident cerebral events.…”
Section: Osa and Related Cvd: Effect Of Cpap Therapymentioning
confidence: 99%